A doação de órgãos no oeste do Paraná: caracterização das doações e do sistema de transplantes da sede da 9ª regional de saúde - Oliveira, Kelen Caroline Lima de (2019)
Organ donation, while not a new subject, remains controversial and delicate to be discussed. Despite the advances in legislation and in the practices of organ transplantation and capture in Brazil, little is known about the reality of organ recruitment in frontier municipalities in Brazil, in relation to the difficulties and challenges faced to effect the donation of organs. In this way, a descriptive and exploratory dissertation was carried out, with quantitative and qualitative data obtained from the Municipal Hospital 'Padre Germano Lauck' (HMPGL) and the Hospital 'Ministro Costa Cavalcanti' (HMCC), both from Foz do Iguaçu, municipality of the 9th regional health center of Paraná, for the period from 2014 to 2017. The objective was to identify the profile of the patients who donated their organs and to understand the reasons for nondonations, as well as information on the flow and the transplant system of the region of Panará. Quantitative data were obtained from hospital records and treated through descriptive statistics. The qualitative data were obtained through a structured interview, and performed in the hospitals, with the nurses secretaries of the Hospital Intrahospital Commission of Organ Donation and Tissue for Transplant (CIHDOTT) of each hospital, recorded and faithfully transcribed, analyzed through the analysis of content. The research was approved by the Ethics Committee in Research with Human Beings of Unioeste. As a result, we obtained 139 potential organ donors in the period analyzed, with the predominance of men (65,5%), and age group of 30-59 years (51,8%) and equal and over 60 years (25,9%), predominantly resident in Foz do Iguaçu (76,3%). Of this total of 139 potential donors, only 58 (41,7%) took place, 81 of which were not funded, mainly due to clinical contraindications (55,6%), family refusal (35,8%) and logistical / structural problems (7,4%). It was found that in both hospitals surveyed there is an active CIHDOTT and in line with other state and federal instances allowing the success of organ harvesting. The main points that need improvement, highlighted by the interviewees are: to create an exclusive sector for CIHDOTT, to have a greater number of professionals, with exclusive dedication to this action, to improve the structuring of teams and means of organ transport in the state of Paraná. It is concluded that the organ harvesting system works in the municipality, but necessary improvements have been identified.